Pengaruh Komitmen Terhadap Respon Auditor atas Tekanan Sosial: Sebuah Eksperimen - Dyah Sih Rahayu; Faisal Faisal (Jurnal Akuntansi dan Auditing Indonesia, 2005)
This paper reports the results of an experiment examining whether social influence pres¬sures within the accounting firm affect auditor’s willingness to sign-off on financial statements that are materially misstated. This paper also examines the effects of organizational commitment, pro¬fessional commitment as variables that may impact individual responses to social influence pres¬sures. A sample of 54 students from Pendidikan Profesi Akuntansi (PPA) participated in a be¬tween-subjects experiment. The results support the hypothesis that obedience pressure signifi¬cantly increased auditor’s willingness to sign-off on account balance that was materially misstated. However, the results failed to support hypothesis that organizational commitment and professional commitment have effect to auditor’s decisions under social influence pressure.Keywords: social influence pressures, commitment, experiment.